Geopolitics and Marginality: Re-imaginations from the South. (March 2014) - Saraswat, Deepika; Meena, Krishnendra
Theorisation in modern geopolitics is replete with instances where certain regions have been accorded a marginal status in various schemes of global political–geographical configurations. Geopolitical ideas propounded by Halford J. Mackinder, Nicholas Spykman and Saul B. Cohen are all evidence of geopolitical visualisation and ordering which advantage certain parts of the world by geo-graphing them as strategically important. This ordering disadvantages certain other areas as less important and, therefore, marginal in the context of international politics. The study here attempts to locate the ascription of marginality in modern geopolitics.